Amyloidosis complicating psoriasis. Issue 680 (June 1982) - Amir-Ansari, B.; Joekes, A. M.; Parkinson, M. C.
Abstract : A man aged 59 years with a 39-year history of psoriasis, for which treatment had included steroids and methotrexate, developed renal failure caused by amyloidosis. Post-mortem revealed widespread amyloid deposits but no evidence of other disease classically associated with amyloidosis.